Dynamics of protein interactions with new biomimetic interfaces: toward blood-compatible biomaterials - Hedayati, Mohammadhasan, author; Kipper, Matt J., advisor; Krapf, Diego, committee member; Reynolds, Melissa, committee member; Bailey, Travis, committee member (Colorado State University. Libraries, 2019)
Nonspecific blood protein adsorption on the surfaces is the first event that occurs within seconds when a biomaterial comes into contact with blood. This phenomenon may ultimately lead to significant adverse biological responses. Therefore, preventing blood protein adsorption on biomaterial surfaces is a prerequisite towards designing blood-compatible artificial surfaces.

This project aims to address this problem by engineering surfaces that mimic the inside surface of blood vessels, which is the only known material that is completely blood-compatible. The inside surface of blood vessels presents a carbohydrate-rich, gel-like, dynamic surface layer called the endothelial glycocalyx. The polysaccharides in the glycocalyx include polyanionic glycosaminoglycans (GAGs). This polysaccharide-rich surface has excellent and unique blood compatibility. We developed a technique for preparing and characterizing dense GAG surfaces that can serve as models of the vascular endothelial glycocalyx. The glycocalyx-mimetic surfaces were prepared by adsorbing heparin- or chondroitin sulfate-containing polyelectrolyte complex nanoparticles (PCNs) to chitosan-hyaluronan polyelectrolyte multilayers (PEMs).

We then studied in detail the interactions of two important blood proteins (albumin and fibrinogen) with these glycocalyx mimics. Surface plasmon resonance (SPR) is a common ensemble averaging technique for detection of biomolecular interactions. SPR was used to quantify the amount of protein adsorption on these surfaces. Moreover, single-molecule microscopy along with advanced particle tracking were used to directly study the interaction of single-molecule proteins with synthetic surfaces. Finally, we developed a groundwork for a kinetic model of long-term protein adsorption on biomaterial surfaces.

In the first chapter, we thoroughly summarize the important blood-material interactions that regulate blood compatibility, organize recent developments in this field from a materials perspective, and recommend areas for future research. In the second chapter, we report the preparation and characterization of dense GAG surfaces that can serve as models of the vascular endothelial glycocalyx. In the third chapter, we investigate how combining surface plasmon resonance, X-ray spectroscopy, atomic force microscopy, and single-molecule total internal reflection fluorescence microscopy provides a more complete picture of protein adsorption on ultralow fouling polyelectrolyte multilayer and polymer brush surfaces, over different regimes of protein concentration. In the fourth chapter, the interactions of two important proteins from the blood (albumin and fibrinogen) with glycocalyx-mimetic surfaces are revealed in detail using surface plasmon resonance and single-molecule microscopy. Finally, in the fifth chapter, the long-term protein interactions with different biomaterial surfaces are studied with single-molecule microscopy and [sentence ends].